Fight : inside the wildest battle for the White House - Allen, Jonathan (Jonathan J. M.); Parnes, Amie (William Morrow & Company, an imprint of HarperCollins Publishers, 2025)
"It was the election America dreaded, a rematch between the two oldest men to serve as president. But somewhere along the way, the 2024 battle for the White House became the most jaw-dropping, heart-pounding, head-turning contest in American history. The ride was so wild that it forced a sitting president to drop his re-election bid, a once and future president to survive felony convictions and a would-be assassin's bullet, and a vice president, unexpectedly thrust into the arena, to mount an unprecedented 107-day campaign to lead the free world. Fight is the backstage story of bloodsport politics in its rawest form -- the clawing, backstabbing, and rabble-rousing that drove Donald Trump into the White House and Democrats into the wilderness. At every turn, the combatants went for the jugular, whether they were facing down rivals in the other party or their own. Bestselling authors Jonathan Allen and Amie Parnes give readers their first graphic view of the characters, their motivations, and their innermost thoughts as they battled to claim the ultimate prize and define a political era. Based on real-time interviews with more than 150 insiders -- from the Trump, Harris, and Biden inner circles, as well as party leaders and operatives -- Fight delivers the vivid and stunning tale of an election unlike any other. In the end, Trump overcame voters' concerns about his personal flaws by tapping into a deep vein of dissatisfaction with the direction of the country. At the same time, Democrats struggled to connect with an electorate that felt gaslit by Biden's insistence that he had delivered economic prosperity -- and his pledge to be a "bridge" president. He tore his party asunder, leaving destroyed personal relationships in his wake, as he clung to power. And when he gave it up, he kneecapped Harris by demanding unprecedented loyalty from her. [...] Allen and Parnes [...] provide readers with a skeleton key to the rooms where it all happened, revealing a story more shocking than previously reported."--HarperCollins website.